Validity and Reliability of the Spanish Version of the Technological Competency as Caring in Nursing Instrument - Rincón Álvarez, Daniel Andrés; Chaparro Díaz, Lorena (Investigación y Educación en Enfermería, 2017)
Objective. This work aimed to evaluate validity and reliability to measure the technological competency of Nursing in Colombia of the Spanish version of the Technological Competency as Caring in Nursing Instrument (TCCNI). Methods. This was a test validation study, which evaluated linguistic, facial, content, and construct validity, besides, the instrument’s reliability. Results. The instrument reported face validity with Lawshe’s index: clarity 0.86, precision 0.83, and comprehension 0.89. Agreement of Fleiss’ kappa index was clarity 0.75, precision 0.72, and comprehension 0.81. Content validity was obtained with Lawshe’s index: relevance of 0.9 and pertinence of 0.9. Agreement of experts with Fleiss’ kappa index was relevance at 0.9 and pertinence at 0.9. For construct validity, 255 nurses participated. Factor analysis generated six factors (Knowing is Caring, Professional and Disciplinary Values of Nursing, Care and Ethics, Technological Competency, Healing and Human Care), which yielded a total accumulated variance of 54.2% and Cronbach’s alpha of 0.88. Conclusion. The TCCNI Spanish version reported a consolidated validity, becoming a viable and reliable instrument to measure the technological competency of Nursing in Colombia. How to cite this article: Rincón DA, Chaparro L. Validity and Reliability of the Spanish Version of the Technological Competency as Caring in Nursing Instrument. Invest. Educ. Enferm. 2017; 35(2):154-164.